Interferon Lambda: Modulating Immunity in Infectious Diseases - Syedbasha, Mohammedyaseen; Egli, Adrian (Frontiers in Immunology, 2017)
Interferon-λs 1-4 (IFNL1-4) modulate immunity in the context of infections and autoimmune diseases, through a complex network of induced genes. IFN-λs act by binding to the hetero-dimeric IFN-λ receptor (IFNLR), activating a STAT-phosphorylation dependent signalling cascade, and thereby inducing hundreds of IFN-stimulated genes modulating various immune functions via complex forward and feedback loops. In contrast to the IFN-α signalling cascade, three important differences have been discovered. Firstly, the IFNLR is not ubiquitously expressed; in particular, immune cells show significant variation in the expression levels and susceptibilities to IFN-λs. Secondly, the binding affinities of individual IFN-λs to the IFNLR strongly varies and are generally lower compared to IFN-α binding affinities. Finally, genetic variation in the form of a series of single nucleotide polymorphisms (SNPs) linked to genes involved in the IFN-λ signalling cascade has been described, and associated with the clinical course and treatment outcomes of hepatitis B and C virus infection. The clinical impact of the IFN-λ signalling and the SNP variations may, however, reach far beyond viral hepatitis. Recent publications show important roles for IFN-λs in a broad range of viral infections such as human T-cell leukemia type-1 virus, rotaviruses and influenza virus. Potentially IFN-λ even modulates the course of bacterial colonization and infections as shown for Staphylococcus aureus and Mycobacterium tuberculosis. Although the immunological processes involved in controlling viral and bacterial infections are highly diverse, IFN-λs may interfere at various levels: as an innate immune cytokine with direct antiviral effects; or as a modulator of the IFN-α induced signalling via the suppressor of cytokine signalling 1 (SOCS1) and the Ubiquitin specific peptidase 18 (USP18) inhibitory feedback loops. In addition, the modulation of adaptive immune functions via macrophage and dendritic cell polarization, and subsequent priming, activation, and proliferation of pathogen-specific T- and B-cells may also be important elements associated with infectious diseases outcomes. This review summarizes the emerging details of the IFN-λ immunobiology in the context of the host immune response and viral and bacterial infections.